Prosedur Penyimpanan Surat Masuk Pada Dinas Perindustrian, Perdagangan, Koperasi, Usaha Kecil Dan Menengah Provinsi Kalimantan Timur - Zuhriah Zuhriah; Gunadi Gunadi (E-BISMARK : Jurnal Ekonomi, Bisnis Dan Marketing, 2021)
The procedure of storing incoming mail is a step of work carried out in connection with the deposit of a warrant and then processed at the Department of Industry, Trade, Cooperatives, Small and Medium Enterprises of East Kalimantan Province. The object of this research is the procedure of storing letters at the Department of Industry, Trade, Cooperatives, Small and Medium Enterprises of East Kalimantan Province. The purpose of this study is to find out how the procedure of storing incoming letters to the Department of Industry, Trade, Cooperatives, Small and Medium Enterprises of East Kalimantan Province. This research was conducted by qualitative descriptive method. The result of this study storage system used in the Department of Industry, Trade, Cooperatives, Small and Medium Enterprises East Kalimantan Province is a storage system based on numbers. According to (Sedarmayanti, 2015) the archive storage system based on numbers is one of the problem group file matching systems that then each or every problem is given a certain number